Aspects of condition in captive and free-ranging dolphins - Young, Deborah Dione (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1999)
Aspects of morphological and physiological condition of captive and net-caught dolphins were studied with respect to age, diet, reproduction and seasonal changes in environmental factors. These investigations aimed to provide base-line data on marine mammal physiological and morphological condition indices and to expand the knowledge of condition assessment of small cetaceans. By examining the interactive nature of animal condition and growth, diet and the environment, the study investigated the potential usefulness of animal condition indices to assess and monitor habitat quality. Base-line values for haematological and blood chemistry parameters were established for five captive bottlenose dolphins (Tursiops truncatus), using monthly blood samples, collected between 1992 and 1995, and corresponding measures of body weight and blubber thickness; feeding, dietary energy intake, water temperature and behavioural and medical records. Curves of best fit were used to interpret trends between leukocytic, haematological and blood chemistry parameters and morphology, diet and water temperature. WBC's and WBC differential cell types were related more distinctly to clinical changes in health, than to condition. RBC, HB and PCV were useful as short-term indicators of nutritional condition, with enhanced haematological status associated with greater food intake and improved diet quality. Weight was a more effective long-term indicator of nutritional status. The importance of blubber thickness measurements as a morphological index of condition was reinforced, with relationships between blubber thickness and haematology highlighting interactions between morphological and physiological condition. The complex interactions between haematology, diet, temperature and weight emphasised the need to account for all influential factors when considering haematological condition. The blood chemistry parameters of serum creatinine, BUN, BUN:creatinine and serum albumin provided the best indication of nutritional condition and diet quality in captive dolphins. Creatinine and BUN:creatinine also reflected changes in morphological condition. Reduced ALP was associated with nutritional stress but was more effectively used as an indication of metabolism and growth activity. LDH and CPK were highly variable and fluctuated with changing activity levels, limiting their use as condition indices. Serum sodium was an important indication of diet quality and hydration status. Many of these parameters effectively illustrated that physiological condition is compromised outside of the thermoneutral zone of the species. Bottlenose and common (Delphinus delphis) dolphins, incidentally caught in shark nets, were used to investigate the condition of free-ranging dolphins. Blood samples, taken as soon as possible after capture from drowned animals, were used to analyse physiological parameters. Dissections provided morphological data. Age and dietary status were assessed using growth layer groups in teeth and stomach content analyses, respectively. Morphological measures of net-caught dolphins reflected important interactions with diet, water temperature and reproductive status. Weight, girth and blubber thickness were valuable indicators of condition, although blubber thickness and proportional blubber weight were the best indicators of nutritional status. Condition of net-caught dolphins was difficult to assess in terms of leukocytic and haematological parameters. Stress- and post-mortem-associated changes, and variable data, reduced the usefulness of some parameters. WBC counts reflected on immunological status and served to emphasise changes in health, which may lead to deterioration in condition. WBC's showed potential as indicators of habitat quality, in terms of parasite load and/or pollution. Interactions between RBC, HB, PCV, MCV and dietary, morphological and environmental factors proved valuable in the short-term. Several haematological parameters were related to morphological condition, with weight, girth and blubber thickness, showing potential as non-invasive predictors of haematological status. Relationships between haematology and water temperature implied that dolphins have physiological and environmental "zones of comfort", within which condition is optimised. LDH and CPK were elevated by capture stress and post-mortem changes. Serum sodium and plasma glucose were good indicators of short-term nutritional status, but were altered by stress, which reduced their usefulness as condition indicators. BUN, albumin, globulin, albumin:globulin, total cholesterol and triglycerides appeared to be little affected by these changes and are potentially valuable indicators of condition in net-caught and/or free-ranging dolphins, particularly with respect to nutritional condition, and associated changes in morphology. Although data were limited, these parameters show the greatest potential as physiological indicators of animal condition and environmental health. The limitations of this study are recognised, however, results highlight the feasibility of using net-caught specimens to monitor the condition of free-ranging marine mammals, and the marine habitat as a whole. Relationships established in this study will be used to elucidate further on the interactive nature of marine mammal condition and aid in the development of a non-invasive condition assessment technique.
Keywords: Dolphins -- Physiology; Dolphins -- Behavior